Identification and prevalence of in vivo-induced genes in enterohaemorrhagic Escherichia coli. Issue 1 (1st January 2019) - Gardette, Marion; Le Hello, Simon; Mariani-Kurkdjian, Patricia; Fabre, Laetitia; Gravey, François; Garrivier, Annie; Loukiadis, Estelle; Jubelin, Grégory
ABSTRACT: Enterohaemorrhagic Escherichia coli (EHEC) are food-borne pathogens responsible for bloody diarrhoea and renal failure in humans. While Shiga toxin (Stx) is the cardinal virulence factor of EHEC, its production by E. coli is not sufficient to cause disease and many Shiga-toxin producing E. coli (STEC) strains have never been implicated in human infection. So far, the pathophysiology of EHEC infection is not fully understood and more knowledge is needed to characterize the "auxiliary" factors that enable a STEC strain to cause disease in humans. In this study, we applied a recombinase-based in vivo expression technology (RIVET) to the EHEC reference strain EDL933 in order to identify genes specifically induced during the infectious process, using mouse as an infection model. We identified 31 in vivo -induced ( ivi ) genes having functions related to metabolism, stress adaptive response and bacterial virulence or fitness. Eight of the 31 ivi genes were found to be heterogeneously distributed in EHEC strains circulating in France these last years. In addition, they are more prevalent in strains from the TOP seven priority serotypes and particularly strains carrying significant virulence determinants such as Stx2 and intimin adhesin. This work sheds further light on bacterial determinants over-expressed in vivo during infection that may contribute to the potential of STEC strains to cause disease in humans.